2018
DOI: 10.1186/s13104-018-3669-y
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of age and body mass index with the level of both protease MMP3 and anti-protease TIMP-1 among Indonesian patients with chronic obstructive pulmonary disease: a preliminary findings

Abstract: ObjectivesIndividuals with chronic obstructive pulmonary disease (COPD) are usually > 50 years of age and have a low body mass index (BMI). An imbalance between matrix metalloproteinases (MMPs), including MMP-3, and tissue inhibitor of metalloproteinase 1 (TIMP-1), play a role in tissue degradation of lung extracellular matrix among COPD individuals. The purpose of the present study was to correlate age and/or BMI with salivary levels of MMP-3 and TIMP-1 among Indonesian subjects with COPD.ResultsThirty COPD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Among smokers without COPD, the activities of MMP-9 and TIMP-1 result in recovery and resolution, whereas for smokers with COPD, this results in ECM destruction and emphysema. However, the preliminary findings of Mulyadi et al [46] suggested that salivary TIMP-1 is not a suitable biomarker in Indonesian subjects with COPD. In our study, TIMP-1 and -2 levels were lower in the control group but were higher in patients with severe COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among smokers without COPD, the activities of MMP-9 and TIMP-1 result in recovery and resolution, whereas for smokers with COPD, this results in ECM destruction and emphysema. However, the preliminary findings of Mulyadi et al [46] suggested that salivary TIMP-1 is not a suitable biomarker in Indonesian subjects with COPD. In our study, TIMP-1 and -2 levels were lower in the control group but were higher in patients with severe COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance between the levels of MMP-9 and TIMP-1 might result in aberrant ECM degradation or the accumulation of ECM proteins in pulmonary alveoli and small airway walls, which could lead to COPD [36]. Further studies with a more heterogeneous population are required to clarify the precise role of TIMPs as a possible biomarker of antiprotease activity in the lung [46].…”
Section: Discussionmentioning
confidence: 99%